Universities’ Strategic Directions for Advancing Health and Medical Education: A Scenario-Based Qualitative Delphi Study - Rita Rezaee; Kimia Pourmohammadi; Azimeh Ghorbanian; Christian Moro; Javad Kojuri; Nasim Salehi (Interdisciplinary Journal of Virtual Learning in Medical Sciences)
Background: Higher education, particularly in the field of medical sciences, has always been influenced by ongoing scientific, technological, and social changes. The emergence of new technologies, the expansion of virtual environments, and unforeseen events such as the COVID-19 pandemic have presented universities with fundamental challenges over the past two decades. In order to adapt to this rapidly evolving world, it is essential for institutions to adopt new orientations and implement innovative, entrepreneurial strategies that leverage flexible and technology-enhanced learning methods. This study aimed to develop strategic recommendations for Iranian medical and health education institutions.Methods: A qualitative Delphi study was conducted in 2020, involving semi-structured interviews with 15 experts across three phases to identify future-oriented directions in medical education, taking into account the challenges posed by the pandemic and its profound effects on educational priorities. In the first phase, an environmental analysis was performed to determine the internal and external factors shaping the future of health education. The second phase focused on forecasting potential trajectories for health education between 2020 and 2030, with the goal of informing possible educational reforms. In the third phase, coherent strategic directions were formulated using structured scenario-building techniques. Thematic content analysis was applied to the interview data, which were analyzed at the levels of statements, components, and categories to extract key themes and insights.Results: The study showed four possible future scenarios. The first scenario advocates for a transition toward an entrepreneurial and research-oriented academic model addressing real-world challenges. The second focuses on integrating flexible and advanced innovative learning systems. The third scenario reflects a gradual adoption of educational technologies and innovative pedagogies. The fourth envisions a regression to conventional education models, solely foundational knowledge without promoting innovation.Conclusion: To support future-oriented, innovation-driven health education systems, universities need to continuously monitor global trends and implement strategic planning frameworks that support adaptable and sustainable educational reform.